Numerical investigation of Aloe Vera-mediated green synthesized CuAlO2 as HTL in Pb-free perovskite solar cells - Sarkar D.K.; Mottakin M.; Hasan A.K.M.; Islam M.A.; Haque M.M.; Selvanathan V.; Aminuzzaman M.; Alanazi A.M.; Akhtaruzzaman M. (Taylor and Francis Ltd., 2025)
This study explores green-synthesized delafossite CuAlO2 as a hole transport layer (HTL) in a CH3NH3SnI3-based perovskite solar cells (PSCs) with an FTO/CuAlO2/CH3NH3SnI3/WO3/Au structure. The performances of the cell have been theoretically investigated using SCAPS-1D. Interface defects significantly impact cell efficiency, as defect density increases from 1014 cm?3 to 1020 cm?3 efficiency reducing from 25.3% to 24.45% in the HTL/perovskite junction and from 25.2% to 17.8% in the perovskite/electron transport layer (ETL) interface. PCBM as buffer layer at perovskite/ETL interface compensates for power conversion efficiency (PCE) losses. Optimizing parameters reveals the delafossite CuAlO2-based, lead-free perovskite solar cell achieving peak efficiency at 26.74%, with VOC, JSC, and FF values of 0.99 V, 33.43 mA cm?2, and 81.05%, respectively. This research underscores delafossite CuAlO2 as a promising HTL for eco-friendly, stable CH3NH3SnI3-based perovskite solar cells, emphasizing its potential in enhancing device performance. ? 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.